Ultraviolet excitation of photoconductivity in thin films of sol-gel SnO2 - Geraldo, V; Scalvi, LVA; Morais, E. A.; Santilli, C. V.; Miranda, P. B.; Pereira, T. J. (Elsevier B.V., 2005)
Tin dioxide (SnO2) thin film photoconductivity spectra were measured for a large temperature range using a deuterium source, the intensity of photocurrent spectra in the range 200-400 nm is temperature dependent, and the photocurrent increases in the ultraviolet even for illumination with photon energies much higher than the bandgap transition. This behavior is related to recombination of photogenerated electron-hole pairs with oxygen adsorbed at grain boundaries, which is consistent with nanoscopic crystallite size of sol-gel deposited films. (c) 2005 Elsevier Ltd. All rights reserved.
Keywords: sol-gel processes; electrical conductivity; sensors; tin dioxide